ASSESSMENT OF THE STATUS OF THE IMMUNE RESPONSE IN PREGNANT WOMEN WITH PLACENTAL INSUFFICIENCY TAKING INTO ACCOUNT THE SEVERITY OF CEREBRAL PATHOLOGY IN THEIR NEWBORN - T. G. Plahotya; V. A. Lindе; M. A. Levkovich; I. I. Krukier; D. I. Sozaeva (Медицинский вестник Юга России, 2013)
Purpose. The study of immunological mechanisms of hypoxic-ischemic brain damage of varying severity in infants born to mothers with placental insufficiency.Materials and methods. A clinical and laboratory examination of 58 pregnant women with placental insufficiency in the period 38-39 weeks of pregnancy. The subjects were divided into subgroups: 1a - perinatal CNS lesions with an average degree of severity, clinically detectable at birth (n = 31), 1b - perinatal CNS damage with mild severity, clinically detectable at 1 month after birth (n = 27). The control group consisted of patients with physiological pregnancy and childbirth (n = 19).Results. It was revealed that the criterion of hypoxic-ischemic central nervous system in newborns is to increase the mother’s blood level of CD16 + NK-cell activation markers of T-cell CD69 +, CD25 +, apoptosis markers CD95 +, AnnexinV +, AnnexinV + PI +, shift the cytokine balance in favor of pro-inflammatory cytokines ( TNF-α, IL -6, IFN-γ), both in serum and amniotic fluid.Conclusions. The development of hypoxic-ischemic brain damage in newborn infants of mothers with placental insufficiency occurs against violations of the mechanisms of immune response.